Looking back on ASEAN and the Sino-US Rivalry in the Cold War - NGOEI, Wen-Qing (WEI Wenqing) (Institutional Knowledge at Singapore Management University, 2021)
In discussions of the current Sino-US rivalry, talk of China eclipsing America as the world’s foremost power is popular. Analysts seeking signs of US decline can certainly muster suitable evidence with which to argue this case. In Southeast Asia, a major theatre of Sino-US competition for influence, trade and security ties, there are serious concerns over which of the two powers will end up predominant in regional affairs. In fact, America and its Southeast Asian allies faced a similar challenge in the Cold War. Then as now, most of the attention was on the big powers. But, the agency of ASEAN statesmen—in particular the influence they exerted upon Sino-US relations—was considerable, even profound. Not only did the anticommunist elites of ASEAN contribute to the susceptibility of Beijing to US rapprochement, but they also shaped the salient principles of Sino-US détente. Far from being bystanders to great power politics, ASEAN leaders played critical roles in this momentous turn of the Cold War. Our understanding of US and Chinese competition in Cold War Southeast Asia remains incomplete without a careful study of the smaller regional actors who, regrettably, have been marginalized by the outsize attention that scholars, journalists and pundits shower upon the agendas and actions of big powers.